Review on Applicable breakup/coalescence models in turbulent liquid-liquid flows - Sajjadi, B.; Abdul Raman, Abdul Aziz; Shah, R.S.S.R.E.; Ibrahim, Shaliza (2013)
Liquid-liquid flows are common in process industries, particularly in turbulent systems. These systems are usually characterized by the diameter of the dispersed phase and are governed by external forces, deformation, breakup, and coalescence processes. In this review, the common methods and equations used to predict these phenomena will be discussed. First, deformation models in both laminar and turbulent flows containing single and multi-drop are considered. Then, the breakup process and models for these mechanisms are investigated. The coalescence process and collisions that may result in coalescence are also investigated. Coalescence efficiency is another factor that will be introduced in this review. Finally, daughter droplet size distribution is investigated considering both phenomenological and statistical models. Copyright Â© 2011-2013 by Walter de Gruyter GmbH.